2012
DOI: 10.1021/la304118b
|View full text |Cite
|
Sign up to set email alerts
|

Probing of Field-Induced Structures and Tunable Rheological Properties of Surfactant Capped Magnetically Polarizable Nanofluids

Abstract: Oil-based nanofluid containing surfactant-capped magnetite nanoparticles are synthesized by a simple coprecipitation approach, and their magnetorheological properties are studied for different magnetic field strengths and volume fractions. We observe a distinct "plateau-like region" in the shear thinning viscosity curve, under an external magnetic field, possibly due to a peculiar alignment of the chains with respect to the field direction where the structure is stable against fragmentation. The observed plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 88 publications
4
45
0
Order By: Relevance
“…The response of fluid under magnetic field is attributed to anisotropic, three-dimensional chain-like structures formed parallel to the direction of applied magnetic field. Therefore, MR fluid exhibits changes in viscosity by several orders of magnitude in presence of field [3][4]. As carrier liquid is entrapped in between the fibrous columnar aggregates of magnetized particles, the effective solid phase concentration increases, therefore, the on-state viscosity jumps up manifolds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The response of fluid under magnetic field is attributed to anisotropic, three-dimensional chain-like structures formed parallel to the direction of applied magnetic field. Therefore, MR fluid exhibits changes in viscosity by several orders of magnitude in presence of field [3][4]. As carrier liquid is entrapped in between the fibrous columnar aggregates of magnetized particles, the effective solid phase concentration increases, therefore, the on-state viscosity jumps up manifolds.…”
Section: Introductionmentioning
confidence: 99%
“…Ferrofluidic systems are colloidal dispersions of superparamagnetic ultra-small (~10 nm) nanoparticles with minimum polydispersity and long term stability [3]. However, very low field-induced mechanical stress limits their usage [6].…”
Section: Introductionmentioning
confidence: 99%
“…[225] The magnetorheological properties of oil-based surfactantcapped Fe 3 O 4 FFs synthesized by the coprecipitation method was analyzed. [193] The formation of columnar structures that hinder the flow behavior was confirmed by the increase in both static and dynamic yield stresses under the magnetic field. Besides, the magnetorheology of FFs can be described using the Mason number (MN).…”
Section: à3mentioning
confidence: 95%
“…[210] Other researchers have also predicted the increase in chain length with increasing l by using the Monte Carlo method, the mean-field Fokker-Planck equation, and molecular dynamics. [193] The homogeneity in FF concentration also has a significant role in determining the magnetic dipolar attraction between the particles. López-López et al demonstrated that when ferromagnetic microparticles are immersed in a FF, the expected magnetic dipolar attraction between them disappears owing to a new repulsive force induced by a local inhomogeneity in MNP concentration among the microparticles.…”
Section: Interaction Parameter and Dipolar Interactionsmentioning
confidence: 99%
See 1 more Smart Citation